The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/jcb.24539
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of ceramide‐induced COX‐2‐dependent apoptosis in human ovarian cancer OVCAR‐3 cells partially overlapped with resveratrol

Abstract: Ceramide is a member of the sphingolipid family of bioactive molecules demonstrated to have profound, diverse biological activities. Ceramide is a potential chemotherapeutic agent via the induction of apoptosis. Exposure to ceramide activates extracellular-signal-regulated kinases (ERK)1/2- and p38 kinase-dependent apoptosis in human ovarian cancer OVCAR-3 cells, concomitant with an increase in the expression of COX-2 and p53 phosphorylation. Blockade of cyclooxygenase-2 (COX-2) activity by siRNA or NS398 corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 61 publications
(118 reference statements)
0
45
0
Order By: Relevance
“…Mechanistically, it has been proposed that the anticancer effect of ASA is mediated through COX-dependent 36,37,57,58 and -independent pathways. 53,54,59 Recent studies have shown that MCF-7 mammospheres are insensitive to the cyclooxygenase pathway, and the COX-2 inhibitor (Indomethacin) was unable to reduce the mammosphere-forming capacity of MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, it has been proposed that the anticancer effect of ASA is mediated through COX-dependent 36,37,57,58 and -independent pathways. 53,54,59 Recent studies have shown that MCF-7 mammospheres are insensitive to the cyclooxygenase pathway, and the COX-2 inhibitor (Indomethacin) was unable to reduce the mammosphere-forming capacity of MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 protein, which is overexpressed in MDA-MB-231 cells, inhibits apoptosis in various cancer cells through the regulation of multiple pathways including Fas-Caspase-3-mediated apoptosis. [36][37][38] Given the constitutive overexpression of COX-2 in MDA-MB-231 cells, we postulated that ASA may negatively regulate COX-2 expression to promote apoptosis signals. However, this is not the case as ASA was unable to regulate COX-2 expression at protein level in MDA-MB-231 cells (Supplementary Figure S4).…”
Section: Dose-dependent Inhibitory Effect Of Asa On Bc Cell Viabilitymentioning
confidence: 99%
“…It is known that A2780/ CP70 cell line has a wild-type p53 gene sequence [47]. Although OVCAR-3 has a point mutation in the p53 gene which results in single amino acid changes, p53 still play an important role in the apoptosis and cell cycle arrest of OVCAR-3 cells induced by some cytokines and compounds [4850]. The present work suggested that ChK regulated p53 at either the transcriptional and translational levels, but not at a post-translational level in OVCAR-3 and A2780/CP70 cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, ceramide levels increase 24-48 h after resveratrol treatment (Scarlatti et al 2003), which correlates with the onset of apoptosis (Delmas et al 2003;Dimanche-Boitrel et al 2005) and suggests de novo changes in the expression of enzymes involved in ceramide metabolism. The mechanisms by which resveratrol and ceramide induce apoptosis in ovarian cancer cells are partially overlapped and involve a COX-2-dependent pathway (Lin et al 2013). Resveratrol also increases dihydroceramide levels by reducing the activity of dihydroceramide synthases in gastric cancer cells (Shin et al 2012).…”
Section: Cancer and Inflammationmentioning
confidence: 99%